Infusoria cultivating methods for marine finfish larvae using vegetables and dry fish powder - Mohd Shahidin, Syafiqah Hanani; Mohammad Noor, Normawaty; Mohd Idris, Shaharah; Mustafa, Sufian; Mukai, Yukinori (UNISZA, 2018)
Seed production of marine finfish in Malaysia is still facing problem particularly live feed for starter diet. Currently, aqua culturists use S or SS type rotifers, which have sizes from 100 to 200μm. Early stage larvae of some marine finfish species select feeds less than 100 μm. Infusoria is a collective term of aquatic microorganism that has been identified to be suitable live feed, as their body sizes are less than 100μm. However, there is no data about basic culture methods. Thus, the objective of this experiment is to study the method of culturing infusoria using batch culture method and continuous culture method. In batch culture method, infusoria were cultured in triplicates for a duration of 2, 4, 6, and 8 days in 500 mL saline water respectively. In this experiment, the nutrients used were powder vegetables (Brassica pekinensis and Brassica chinensis) and powdered anchovies. The nutrients were only given at the first day of experiment. In continuous culture method, infusoria were cultured in the beakers for a duration of 11 days in triplicates. Every day, 10%, 20%, and 30% of cultured water were harvested from the beaker. After that, the same amount of saline water and nutrients were added in the beaker. For the results of batch culture method, the highest total harvested was in 4 days which was 2,690,000 ind/500 mL. Followed by, 2 days with 2,480,000 ind/500 mL, 6 days with 607,000 ind/500 mL, and 8 days with 202,000 ind/500 mL. The results for continuous culture method showed that the total harvested in 11 days were 777,250 ind in 10%, 1,123,000 ind in 20%, and 814,500 ind in 30% respectively. Based on the results, the recommended cultivation period for batch culture method was 4 days. For continuous culture method, the recommended harvesting amount per day was 20%.